Knowledge, attitude and practices of women towards breast cancer in the field practice area of urban health training centre, Aurangabad, Maharashtra - Paunikar, Apeksha P.; khadilkar, Hrishikesh A.; Doibale, Mohan K.; Kuril, Bina M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Breast cancer accounts for 19-34% of all cancer cases among women in India. There is a high mortality as patients usually present at an advanced stage because of lack of awareness and nonexistent breast cancer screening programs. So the aim of study is to know knowledge, attitude and practices (KAP) of women towards breast cancer in the field practice area of urban health training centre (UHTC). Methods: A cross sectional study included 140 women of age ≥15 years residing in field practice area from October 2016 to January 2017. From four wards in the field practice area, equal samples were drawn from each ward. Data was collected using questionnaires designed to elicit socio-demographic information and knowledge, attitude and practices of these women towards breast cancer. Data analysis was done by Open Epi. Results: Out of 140 women interviewed, 78.57% mentioned at least one of the symptoms of breast cancer but only 37.86% identified painless lump as a symptom. Only 46.43% mentioned any one of the risk factors. More educated and younger age women were more knowledgeable about risk factors. 44.29% participants were aware of early detection measures but very few were actually practicing SBE, CBE. CBE was most common tool identified for detection. Conclusions: Women do have KAP deficits of breast cancer. So community oriented awareness generation programs to educate women about breast cancer, to promote early detection of breast cancer and to bring about the desirable behavioural change among women is needed.